The superluminous vacuum - Markoulakis, Emmanouil (International Journal of Physical Research, 2023)
The Standard Cosmological and Particle Models of physics have set both in their formalism an absolute limit, the speed of light c or else called the speed of causality and claim that this is also a physical limit in nature in our visible Universe. This however, we claim is also unproven up to today and nature has always imposed exceptions and violations in accepted theories many times in the past and proved that these were merely human formalism and experiments artifacts and used technology restrictions and that physical limits and rules are constantly broken and bend in nature. We hereby will try to theoretically demonstrate, why and how the very existence and empirical evidence in our Universe of vacuum space, either in its theorized ideal absolute form thus free space or partially vacuum characterized as QED or QCD vacuum and its zero-point energy and fluctuations, maybe actually the biggest proof in nature for superluminous energy being possible without violating causality. That the apparent effect of “nothingness” of vacuum space maybe the evidence for superluminocity and was right in front of us all this time hidden. We herein try to answer a fundamental physics question why vacuum space appears to us, basically, as nothing assuming that ‘nothing’ does not exists in nature and why a hypothetical superluminous vibration, Planck sized particle generates apparent nothingness in our spacetime. The novelty of the research herein infers that free space is the dark energy and which is superluminous energy.